1996
DOI: 10.1111/j.1365-2788.1996.tb00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenging behaviour: the effectiveness of specialist support teams

Abstract: Two specialist community services for people with learning disabilities and challenging behaviour were evaluated over approximately 3 years. Intervention effectiveness was assessed with respect to changes in subjects' skills, challenging behaviours, mental health and quality of life, and to changes in staff morale. Subjects assessed as having challenging behaviour but not referred for specialist input were also studied. Comparison of changes in referred and non-referred samples over time showed minor differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 8 publications
1
43
2
Order By: Relevance
“…Here, however, we note the limited evidence of impact in the Minnis and Devine study (2001, p. 47) at 9 months, and suggest that there are no proven predictors of appropriate time lapse (see Lowe et al 1996). Various possible explanations can be offered.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Here, however, we note the limited evidence of impact in the Minnis and Devine study (2001, p. 47) at 9 months, and suggest that there are no proven predictors of appropriate time lapse (see Lowe et al 1996). Various possible explanations can be offered.…”
Section: Discussionmentioning
confidence: 58%
“…For example, Lowe et al (1996), in their evaluation of peripatetic specialist challenging behaviour teams for people with learning disabilities, found that carers' assessments of presenting behaviours altered positively, in the absence of any observed evidence of behavioural improvement. Carers' ability to cope is fundamental to placement maintenance or breakdown, regardless of behavioural change.…”
Section: Discussionmentioning
confidence: 99%
“…They found that 75% of 134 interventions resulted in improvements in behavior. A case-control study (9) compared outcomes of 14 individuals who received specialist intervention by a "peripatetic" multidisciplinary team with a randomly selected group of 12 individuals who received standard care. The intervention comprised individualized assessment and management plans.…”
mentioning
confidence: 99%
“…As noted by Stancliffe et al (1999a), "specialist community behavior support teams are of limited effectiveness if nonspecialist ID services are ineffective in day-today management of challenging behavior'' (p. 482). Research on the impact of specialist teams, which exist in the United Kingdom and to some (unknown) extent in the United States, has been mixed, variable across teams, and not entirely encouraging (Emerson & Forrest, 1996;Lowe, Felce, & Blackman, 1996). Emerson and Forrest (1996) conducted a survey of community support teams for people with ID and problem behaviors in England and Wales, which they estimated to employ about 450 staff, at a cost of £10 million to serve about 2000 people yearly.…”
Section: Recent Relevant Evaluationsmentioning
confidence: 99%